Bayt Bin ʿĀtī in the Qaṭṭārah oasis: a prehistoric industrial site and the formation of the oasis landscape of al-ʿAin, UAE - Power , Timothy; Sheehan, Peter (Proceedings of the Seminar for Arabian Studies, 2011)
The Bayt Bin ʿĀtī al-Darmakī comprises a mud-brick tower and domestic enclosure located on a mound overlooking the date-palm gardens of the Qaṭṭārah oasis. Archaeological evaluation and monitoring accompanied a redevelopment project of the Abu Dhabi Authority for Culture and Heritage (ADACH) to create the Qaṭṭārah Community Arts Centre within the limits of the structure. Bin ʿĀtī is among the first sites to have been examined within the palm gardens of the al-ʿAin (Buraimī) oasis and therefore offers a new perspective on human activity in the area. The archaeology is characterized for the most part by pits, postholes and ditches associated with large quantities of abraded sherds. This amounts to an archaeology of landscape that complements the nearby settlement sites of Hīlī and Rumaylah. Bin ʿĀtī is further distinguished by the depth of stratigraphy. Excavation revealed a 5 m archaeological sequence, including the following principal horizons: (i) Earlier Iron Age industrial installations; (ii) an Iron Age field system; (iii) later Iron Age copper production; (iv) Early Islamic (ʿarīsh) settlement; (v) two Late Islamic mud-brick houses, the larger including a mud-brick tower (murabbaʿ) and date-presses (madābis,sg. madbasāh), with an unexcavated section of the Qaṭṭārah cemetery. A full publication of Bin ʿĀtī is now in progress, including a quantified study of the ceramics and survey of the Qaṭṭārah oasis. The Iron Age industrial installations have been preserved in situ within a specially redesigned basement and will be presented to the public as part of the wider interpretation of the archaeology of the site.